Desenvolvimento de Tecnologia Educacional sobre cuidados em Saúde Mental na Atenção Primária à Saúde - Boaventura, Lilian César Salgado (2019)
Mental disorders affect more and more people, imposing substantial costs on individuals, families, communities and health systems. And, despite the broad movement of the Psychiatric Reform, little has been done to establish new community-based mental health care practices in which Primary Health Care (PHC) should be a major co-adjuvant. Thus, an integrative review of the literature was carried out in order to identify the main obstacles that make it difficult to care for the person suffering from mental illness in primary care. Seventeen articles were selected through the virtual health databases that showed as main obstacles: maintenance of the traditional psychiatric model, lack of mental health training, lack of network articulation between APS and RAPS, absence of promotion actions mental health, the incipient use of resources available in PHC, stigmatized conceptions of the person in mental distress by the health team, and non-recognition of PHC as a place of care in mental health. Based on these evidences, in a second stage, a prototype of educational technology was elaborated for the educational-caring action of PHC professionals, seeking to raise awareness and awareness about this issue, in an attempt to change this situation so unfavorable to the person with the disorder mental. Therefore, it is fundamental to invest in primary care teams as a strategy to improve the quality of mental health care in the Brazilian population.